Sintered metal porous material, method for producing the same, and use thereof

CN118253776BActive Publication Date: 2026-10-30SICHUAN SIDANENG ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410289610.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2026-10-30
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

[0005]本发明的一个目的在于提供烧结金属多孔材料及其制备方法和应用,以解决现有技术中镍合金材料存在的过电位高、电压稳定性差、强度低、耐腐蚀较差的技术问题

Benefits of technology

(1)合金材料的析氢机理主要运用的是Engel-Brewer的“火山”理论,即d轨道未充满或半充满的过渡系左边的金属同具有成对的但在纯金属中不适合成键的d电子的过渡系右边的金属熔成合金时,对析氢反应可以产生非常明显的电催化协同作用。在本发明中,V位于第四族,是早期过渡金属元素,Ni位于第10族,是后期过渡金属元素,早期和晚期过渡金属元素的协同作用可以有效降低重要中间体(OH*,O*,OOH*)的反应能垒,大大提高整体水裂解效率。并且,V的价态具有多样性,能够促进电荷转移,对Ni电子密度的增加有显著的促进作用,因此,Ni和V的组合可以调节表面电荷状态,使V的电子转移到Ni上,促进协同效应,丰富活性位点,从而提高析氢反应的催化活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118253776B_ABST
    Figure CN118253776B_ABST
Patent Text Reader

Abstract

The application discloses a sintered metal porous material and a preparation method and application thereof, and solves the technical problems of high overpotential, poor voltage stability, low strength and poor corrosion resistance of nickel alloy materials in the prior art. The metal elements of the sintered metal porous material are composed of Ni and V, and the metal elements mainly exist in the form of intermetallic compounds. The preparation method of the sintered metal porous material comprises the following steps: Ni powder and V powder are mixed by ball milling to obtain mixed powder; a forming aid is added into the mixed powder, then granulation and sieving are carried out to obtain forming particles; the forming particles are pressed to form a blank; and high-temperature sintering treatment is carried out on the blank, and the sintered metal porous material is obtained by cooling in the furnace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of hydrogen production by water electrolysis, and more specifically, to sintered porous metal materials, their preparation methods, and applications. Background Technology

[0002] With the increasing global energy consumption, fossil fuels and other energy sources will become increasingly depleted and have a serious negative impact on the environment. Daily life and industrial production generate large amounts of wastewater. Most of this wastewater contains pollutants exceeding safe levels and cannot be directly discharged, requiring wastewater treatment. From another perspective, with the development of the hydrogen energy industry, the demand for hydrogen is gradually increasing. If the aforementioned wastewater could be used to produce hydrogen, it could potentially turn a burden into a source of energy. The development and use of hydrogen energy will usher humanity into an era of sustainable development, and large-scale, inexpensive hydrogen production is a crucial prerequisite for its development and utilization. Among numerous hydrogen production methods, water electrolysis offers low cost, pollution-free products, and significant technological advantages.

[0003] First, traditional wastewater-to-hydrogen processes require purification of organic matter in the wastewater (usually through biochemical reactions and Fenton reactions). This reduces the adverse effects of organic matter on electrode materials, but it leads to a lengthy water treatment process and high energy consumption. Second, to achieve the highest possible current density and lowest hydrogen evolution overpotential under a given electrical energy, electrode materials need to possess characteristics such as high surface area, high conductivity, good catalytic activity, long-term mechanical and chemical stability, and low cost and safety. Generally, noble metals such as Pt, Pd, and Au are considered to have excellent and efficient electrocatalytic hydrogen evolution performance. However, hydrogen production by electrolysis in alkaline water involves multiple water dissociation processes, and the reaction rate is much lower than in acidic systems. Even with noble metal electrodes, the improvement in hydrogen production efficiency in alkaline water electrolysis is very limited. Furthermore, noble metals are scarce and expensive, hindering large-scale industrial production. Therefore, it is necessary to develop highly active and stable non-noble metal catalysts suitable for alkaline water electrolysis.

[0004] Therefore, researchers have done a great deal of work in the selection and design of cathode materials. Nanocrystalline materials, rare earth alloys, and amorphous materials can all be used as cathode materials with good performance. Among them, nickel alloys are one of the most thoroughly studied cathode materials due to their simple preparation methods, wide variety of choices, and excellent catalytic performance. However, current nickel alloy materials have high overpotentials, poor voltage stability, low strength, and poor corrosion resistance, and are still not suitable for alkaline water environments. Summary of the Invention

[0005] One objective of this invention is to provide sintered porous metal materials, their preparation methods, and applications, to solve the technical problems of high overpotential, poor voltage stability, low strength, and poor corrosion resistance in existing nickel alloy materials. Another objective of this invention is to provide water treatment methods and systems to solve the technical problems of long process times and high energy consumption in existing wastewater-to-hydrogen production processes.

[0006] To achieve the above objectives, according to a first aspect of the present invention, a sintered metal porous material is provided, the technical solution of which is as follows: Sintered porous metal materials, the metal elements being composed of Ni and V, and the metal elements mainly existing as intermetallic compounds.

[0007] As a further improvement to the above-mentioned sintered metal porous material: the intermetallic compound is Ni3V and Ni2V3; or, the intermetallic compound is Ni2V; or, the intermetallic compound is Ni2V and NiV3.

[0008] To achieve the above objectives, according to a second aspect of the present invention, a method for preparing sintered metal porous materials is provided, the technical solution of which is as follows: The preparation method of sintered porous metal materials includes the following steps: Ni powder and V powder are ball-milled and mixed to obtain a mixed powder; Add a forming aid to the mixed powder, then granulate and sieve to obtain shaped granules; The shaped particles are pressed into shape to obtain a blank; The billet is subjected to high-temperature sintering and then cooled in the furnace to obtain sintered porous metal material.

[0009] As a further improvement to the above-mentioned method for preparing sintered porous metal materials: the particle size of Ni powder and V powder is 3-20 μm; the forming aid is stearic acid or polyvinyl butyral, and the amount of forming aid is 2-5% of the mass of the mixed powder; sieving is done with a 40-80 mesh sieve; and the material is pressed and formed under a pressure of 50-300 MPa.

[0010] As a further improvement to the above-mentioned method for preparing sintered porous metal materials, the high-temperature sintering process is as follows: starting from room temperature, the temperature is raised to the sintering temperature of 950-1050℃. During this process, the temperature is held for 20-100 minutes after each increase of 50-150℃. After reaching the sintering temperature, the temperature is held for 80-230 minutes. The sintered porous metal material is then obtained by cooling in the furnace.

[0011] As a further improvement to the above-mentioned method for preparing sintered porous metal materials, the high-temperature sintering process is as follows: First stage: Raise the temperature from room temperature to 300-400℃ and hold for 40-80 minutes; Second stage: Continue to heat to 450-500℃ and hold for 40-80 minutes; Third stage: Continue to raise the temperature to 550-600℃ and hold for 40-80 minutes; Fourth stage: Continue to raise the temperature to 650-700℃ and hold for 40-80 minutes; Fifth stage: Continue heating to 750-800℃ and hold for 40-80 minutes; Stage 6: Continue heating to 850–900℃ and hold for 40–80 minutes; Stage 7: Continue heating to 950–1050℃ and hold for 80–230 minutes.

[0012] As a further improvement to the above-mentioned method for preparing sintered porous metal materials: the seventh stage is divided into two stages, specifically: Phase 1: Continue heating to ≥950 and ≤1000℃, and hold for 40–80 minutes; Phase 2: Continue heating to >1000 and ≤1050℃, and hold for 80-150 minutes.

[0013] As a further improvement to the above-mentioned method for preparing sintered porous metal materials: the heating rate from the first stage to stage 1 is 4 to 6 °C / min, and the heating rate from stage 2 is 2 to 4 °C / min.

[0014] To achieve the above objectives, according to a third aspect of the present invention, an electrolytic hydrogen production apparatus is provided, the technical solution of which is as follows: An electrolytic hydrogen production apparatus has a cathode, which is made of the sintered metal porous material described in the first aspect above, or a sintered metal porous material prepared by the preparation method described in the second aspect above.

[0015] To achieve the above objectives, according to a fourth aspect of the present invention, a method for producing hydrogen by electrolysis is provided, the technical solution of which is as follows: An electrolytic hydrogen production method includes the step of: electrolyzing an electrolyte using the electrolytic hydrogen production apparatus described in the third aspect above.

[0016] To achieve the above objectives, according to a fifth aspect of the present invention, a water treatment method is provided, the technical solution of which is as follows: Water treatment methods, including the following steps: Wastewater is pretreated to obtain an electrolyte with solid content, salt content, and pH that meet the requirements for electrolysis. The electrolyte is fed into the electrolytic cell of the electrolytic hydrogen production device for electrolytic treatment, which decomposes the organic matter in the electrolyte and produces hydrogen gas. The cathode of the electrolytic hydrogen production device is made of the sintered metal porous material described in the first aspect above.

[0017] As a further improvement to the above water treatment methods: wastewater is treated by flotation and / or filtration to obtain an electrolyte with a solid content that meets the requirements for electrolysis; wastewater is treated by any combination of softening, membrane separation, ion exchange, and electrodialysis to obtain an electrolyte with a salt content that meets the requirements for electrolysis; wastewater is treated by acidic or alkaline reagents to obtain an electrolyte with a pH that meets the requirements for electrolysis.

[0018] As a further improvement to the above water treatment method: the pretreatment further includes adding chloride ions to the wastewater; the pretreatment further includes adsorption treatment of the wastewater; the solid content of the electrolyte is less than or equal to 1 mg / L, the salt content is ≤15 g / L, and the pH is 12-14.

[0019] As a further improvement to the above water treatment method, it also includes recycling valuable resources from the electrolyzed liquid before discharging the treated water, and / or, it also includes removing impurities from the electrolyzed liquid before discharging the treated water.

[0020] As a further improvement to the above water treatment method: the valuable resource recovery treatment includes concentration treatment and evaporation crystallization treatment; the impurity removal treatment includes any of the following: softening treatment, filtration treatment, and disinfection treatment.

[0021] As a further improvement to the above water treatment method, the cathode of the electrolytic hydrogen production device adopts a titanium-based metal oxide coated electrode.

[0022] To achieve the above objectives, according to a sixth aspect of the present invention, a water treatment system is provided, the technical solution of which is as follows: A water treatment system includes: a pretreatment unit for pretreating wastewater to obtain an electrolyte with solid content, salinity, and pH that meet the requirements for electrolysis; and an electrolytic hydrogen production unit for electrolyzing the electrolyte to decompose organic matter in the electrolyte and generate hydrogen gas. The electrolytic hydrogen production unit includes an electrolytic hydrogen production device, which includes an electrolytic cell shell, an anode, and a cathode. The anode and cathode are alternately arranged. The anode is installed inside the electrolytic cell shell and is used to decompose organic matter in the electrolyte through an anode electrochemical reaction. The cathode is installed inside the electrolytic cell shell and is used to generate hydrogen gas through a cathode electrochemical reaction. The cathode is made of the sintered metal porous material described in the first aspect above.

[0023] As a further improvement to the above water treatment system: the cathode is a hollow structure with a shell and a hollow layer, the hollow structure has an opening, the electrolytic cell shell is provided with an exhaust structure, and hydrogen is output through the exhaust structure.

[0024] As a further improvement to the above-mentioned water treatment system: the shell layer includes a cathode layer and a diaphragm layer manufactured as one piece and arranged from the inside out, the cathode layer being a sintered porous metal material, and the diaphragm layer being formed by a diaphragm material attached to the outer surface of the cathode layer.

[0025] The sintered porous metal material, its preparation method, and its application of the present invention have the following advantages: (1) The hydrogen evolution mechanism of the alloy material mainly utilizes Engel-Brewer's "volcano" theory, that is, when a metal on the left side of the transition system with unfilled or half-filled d orbitals melts into an alloy with a metal on the right side of the transition system that has paired d electrons but is not suitable for bonding in pure metals, a very significant electrocatalytic synergistic effect can be produced on the hydrogen evolution reaction. In this invention, V is located in Group 4 and is an early transition metal element, while Ni is located in Group 10 and is a late transition metal element. The synergistic effect of early and late transition metal elements can effectively reduce the reaction energy barrier of important intermediates (OH*, O*, OOH*), greatly improving the overall water splitting efficiency. Furthermore, V has diverse valence states, which can promote charge transfer and significantly promote the increase of Ni electron density. Therefore, the combination of Ni and V can regulate the surface charge state, allowing electrons from V to transfer to Ni, promoting the synergistic effect, enriching active sites, and thus improving the catalytic activity of the hydrogen evolution reaction.

[0026] (2) Compared with elemental metals and disordered solid solution alloys, the metal elements in the sintered porous metal material of the present invention mainly exist as intermetallic compounds. The intermetallic compounds are composed of metal elements and non-metal elements in a specific ratio. Due to the existence of mixed bonds of metal bonds and covalent bonds, the electronic structure of the material can be further optimized. On the one hand, it has significantly better strength and corrosion resistance. On the other hand, it can promote the adsorption and release of ions during the electrolytic hydrogen production process, reduce the dissociation energy barrier of water in the electrolyte system, improve the hydrogen production efficiency in the electrolyte system, and exhibit good catalytic activity and stability.

[0027] (3) The sintered metal porous material prepared by the elemental powder reaction synthesis method of the present invention has micron-sized pores, which can greatly improve the specific surface area of ​​the material and provide sufficient active sites. At the same time, the micron-sized pores provide channels for hydrogen to escape, avoiding the enrichment of hydrogen on the electrode surface and covering the catalytic active sites.

[0028] (4) The present invention employs a special sintering process. Firstly, it ensures that the phases formed by full sintering are as many as possible as intermetallic compounds, reducing the content of other impurities such as solid solution alloys, metallic elements, carbon elements, carbides, and carbon oxides, resulting in a simple structure, uniform composition, and uniform distribution of all constituent elements without segregation. Secondly, it ensures that the material does not deform, but shrinks or expands proportionally, without local melting or bending. Thirdly, it ensures that a large number of pores are generated in the material to increase the specific surface area, thereby improving the reaction efficiency. Fourthly, it improves the sintering efficiency.

[0029] (5) The water treatment method and system of the present invention directly utilize the anodic electrochemical reaction of the electrolytic hydrogen production device to generate highly active free radicals to decompose organic matter in the water (for example, chloride ions in the wastewater lose electrons at the anode to become chlorine gas, which hydrolyzes into chloride ions and hypochlorous acid, and hypochlorous acid generates hydroxyl radicals ·OH that can deeply oxidize and remove organic matter) and utilize the cathodic electrochemical reaction to generate clean energy hydrogen. Therefore, there is no need for a complex, time-consuming, energy-intensive, and space-consuming organic matter pretreatment process. The overall water consumption is small, saving on reagent costs and subsequent treatment costs. No other metal ions are introduced, and the generated hydrogen can generate more economic benefits. Green electricity can fully meet the demand, resulting in lower electricity costs and significant overall economic benefits. Pretreatment of the wastewater to control the solid content, salinity, and pH before electrolysis can effectively improve electrolysis efficiency. It has been verified that the water treatment method and system of the present invention can degrade the organic matter content in the electrolyte to below 100 mg / L, which can improve the subsequent recovery efficiency of valuable resources and the efficiency of impurity removal.

[0030] Therefore, the sintered porous metal material, its preparation method, and its application of the present invention, by simplifying the formula and improving the sintering process, enable the obtained sintered porous metal material to be used as a cathode material for electrolytic hydrogen production. This material not only has a lower overpotential than commercial Pt / C electrodes and exhibits smaller voltage fluctuations over long-term use, but also maintains stable catalytic activity. Furthermore, it possesses high strength and good corrosion resistance, significantly improving the efficiency and service life of electrolytic hydrogen production. It is an excellent cathode material for electrolytic hydrogen production, effectively solving the technical problems of high overpotential, poor voltage stability, low strength, and poor corrosion resistance found in existing nickel alloy materials, and thus has strong practicality.

[0031] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0032] The accompanying drawings, which form part of this invention, are used to aid in understanding the invention. The contents provided in the drawings and their descriptions in relation to the invention can be used to explain the invention, but do not constitute an improper limitation of the invention.

[0033] Figure 1 The image shows the XRD pattern of the sintered porous metal material obtained in Example 1.

[0034] Figure 2 The image shows the XRD pattern of the sintered porous metal material obtained in Example 2.

[0035] Figure 3 The image shows the XRD pattern of the sintered porous metal material obtained in Example 3.

[0036] Figure 4 The image shows the XRD pattern of the sintered porous metal material obtained in Example 4.

[0037] Figure 5 The XRD pattern of the sintered porous metal material obtained in Comparative Example 1 is shown.

[0038] Figure 6 The cathode constant current polarization stability test curve of the sintered metal porous material in Example 3 is shown.

[0039] Figure 7 The CV cycle curve is shown for the sintered porous metal material of Example 3.

[0040] Figure 8 This is a diagram of the double-layer capacitance of the sintered porous metal material in Example 3.

[0041] Figure 9 This is a SEM image of the sintered porous metal material of Example 3.

[0042] Figure 10 This is a backscattered scanning electron microscope image of the sintered porous metal material of Example 3.

[0043] Figure 11 This is a schematic diagram of the structure of the first embodiment of the electrolytic hydrogen production device of the present invention.

[0044] Figure 12 for Figure 11 A schematic diagram of the section after cutting the AA section.

[0045] Figure 13 for Figure 12 A schematic diagram of the electrolytic hydrogen production device from another angle.

[0046] Figure 14 for Figure 11 A schematic diagram of the outer shape of the intermediate cathode.

[0047] Figure 15 for Figure 11Schematic diagram of the material layer structure of the central cathode.

[0048] Figure 16 This is a schematic diagram of the anode and cathode in a second embodiment of the electrolytic hydrogen production apparatus of the present invention.

[0049] Figure 17 for Figure 16 A schematic diagram of the structure shown from another angle.

[0050] Figure 18 This is a schematic diagram of the water treatment system structure used in the first embodiment of the water treatment method of the present invention.

[0051] Figure 19 This is a schematic diagram of the process for lithium extraction from salt lakes using the extraction method.

[0052] Figure 20 This is a schematic diagram of the water treatment system structure used in the second embodiment of the water treatment method of the present invention.

[0053] The reference numerals in the attached drawings are as follows: 11-Electrolytic cell shell, 12-Anode, 13-Cathode, 14-Aeration device, 15-Foam removal mechanism, 16-Water distributor, 17-Gas-liquid separator, 111-Electrolysis zone, 112-Air flotation zone, 113-Cathode mounting interface structure, 131-Shell layer, 132-Hollow layer, 133-Opening, 1311-Cathode layer, 1312-Diaphragm layer. Detailed Implementation

[0054] The present invention will now be clearly and completely described in conjunction with the accompanying drawings. Those skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the accompanying drawings, it should be particularly noted that: The technical solutions and features provided in the various parts of this invention, including the following description, can be combined with each other without conflict.

[0055] Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.

[0056] Regarding the terminology and units used in this invention: The terms "comprising," "having," and any variations thereof in the specification, claims, and related parts of this invention are intended to cover non-exclusive inclusion.

[0057] Example 1: The preparation method of the sintered metal porous material in this example includes the following steps: (1) Ni powder and V powder are ball-milled and mixed to obtain a mixed powder; wherein the particle size of Ni powder and V powder is 3-5 μm, the mass ratio of Ni powder to V powder is 33:67, and the ball milling time is 12h.

[0058] (2) Add a forming aid to the mixed powder, then granulate and sieve to obtain shaped granules; wherein, the forming aid is stearic acid, the amount of forming aid is 3% of the mass of the mixed powder, and a 60-mesh sieve is used for sieving.

[0059] (3) The forming particles are pressed into shape to obtain a blank; wherein, under a pressure of 200MPa, 2g of forming particles are pressed into a rectangular blank with a size of 25*8*2mm.

[0060] (4) The billet is subjected to high-temperature sintering treatment and cooled in the furnace to obtain sintered metal porous material.

[0061] The high-temperature sintering process is as follows: First stage: Heat from room temperature to 400℃ at a rate of 5℃ / min, and hold for 60min; Second stage: Continue to heat up to 500℃ at a heating rate of 5℃ / min, and hold for 60min; Third stage: Continue to heat up to 600℃ at a rate of 5℃ / min, and hold for 60min; Fourth stage: Continue heating to 700℃ at a rate of 5℃ / min, and hold for 60min; Fifth stage: Continue heating to 800℃ at a rate of 5℃ / min, and hold for 60min; Stage 6: Continue heating to 900℃ at a rate of 5℃ / min, and hold for 60min; Stage 7: Continue heating to 950℃ at a rate of 3℃ / min, and hold for 90 minutes.

[0062] Figure 1 The image shows the XRD pattern of the sintered porous metal material obtained in Example 1. Figure 1 It can be seen that the main phase is Ni3V, containing a small amount of Ni2V3. In addition to the characteristic peaks of Ni3V and Ni2V3, there are only a small amount of characteristic peaks of vanadium oxide and carbon oxide. The content of impurity peaks is very low, indicating that the sintered porous metal material is composed of Ni-V intermetallic compounds.

[0063] Example 2: Compared with Example 1, the difference in the preparation method of the sintered metal porous material in this example is that the mass ratio of Ni powder to V powder is 55:45; Seventh stage: continue to heat up to 980℃, the heating rate is 3℃ / min, and hold for 110min.

[0064] Figure 2 The image shows the XRD pattern of the sintered porous metal material obtained in Example 2. Figure 2 It can be seen that the main phase is Ni2V, containing a small amount of NiV3. In addition to the characteristic peaks of Ni2V and NiV3, there are only a small amount of characteristic peaks of elemental vanadium. The content of impurity peaks is very low, indicating that the sintered porous metal material is composed of Ni-V intermetallic compounds.

[0065] Example 3: Compared with Example 1, the difference in the preparation method of the sintered metal porous material in this example is that the mass ratio of Ni powder to V powder is 50:50; Seventh stage: continue to heat up to 1000℃, the heating rate is 3℃ / min, and the holding time is 110min.

[0066] Figure 3 The image shows the XRD pattern of the sintered porous metal material obtained in Example 3. Figure 3 It can be seen that the main phase is Ni2V, containing a small amount of NiV3. In addition to the characteristic peaks of Ni2V and NiV3, there are only a small amount of characteristic peaks of elemental vanadium. The content of impurity peaks is very low, indicating that the sintered porous metal material is composed of Ni-V intermetallic compounds.

[0067] Example 4: Compared with Example 1, the difference in the preparation method of the sintered porous metal material in this example is that the mass ratio of Ni powder to V powder is 50:50; the seventh stage is divided into two stages, specifically: Stage 1: Continue heating to 1000℃ at a rate of 5℃ / min, and hold for 60min; Phase 2: Continue heating to 1050℃ at a rate of 3℃ / min, and hold for 110 minutes.

[0068] Figure 4 The image shows the XRD pattern of the sintered porous metal material obtained in Example 4. Figure 4 It can be seen that, apart from the characteristic peak of Ni2V, there are almost no other impurity peaks, indicating that the sintered porous metal material is composed of Ni2V, an intermetallic compound with high purity.

[0069] Comparative Example 1: Compared with Example 1, the difference in the preparation method of the sintered metal porous material in this comparative example is that the mass ratio of Ni powder to V powder is 50:50; Seventh stage: continue to heat up to 910℃, the heating rate is 3℃ / min, and the holding time is 110min.

[0070] Figure 5 The image shows the XRD pattern of the sintered porous metal material obtained in Comparative Example 1. From... Figure 5 It can be seen that the main phases are elemental nickel and elemental vanadium, with only a small amount of the intermetallic compound Ni2V.

[0071] Comparative Example 2: Compared with Example 1, the difference in the preparation method of the sintered porous metal material in this comparative example is that the mass ratio of Ni powder to V powder is 50:50; the seventh stage: continue heating to 1100℃ at a heating rate of 3℃ / min, and hold for 110min. It was verified that the main phase is the intermetallic compound Ni₂V.

[0072] Comparative Example 3: Compared with Example 1, the preparation method of the sintered porous metal material in this comparative example differs in that the mass ratio of Ni powder to V powder is 50:50; the high-temperature sintering process is as follows: heating from room temperature to 400℃ at a heating rate of 5℃ / min, holding for 120min; then further heating to 950℃ at a heating rate of 3℃ / min, holding for 90min. Verification showed that no characteristic peaks of Ni-V intermetallic compounds were detected; the main peaks were those of solid solution alloys, elemental metals, elemental carbon, carbides, and carbon oxides.

[0073] The electrochemical properties, corrosion resistance and yield strength of the sintered metal porous materials of Examples 1-4 and Comparative Example 3 were then tested, and the test results are shown in Table 1.

[0074] The electrochemical performance was tested as follows: An electrochemical workstation was used to test the electrochemical performance of the material. The working electrode of the three-electrode system was the prepared sintered porous metal material (referred to as the NiV electrode), and the reference electrode was a mercury / mercury oxide electrode. The reference electrode was aligned with the center of the working electrode test surface through a capillary (salt bridge) and separated by 1-2 mm. The auxiliary electrode was a platinum sheet (10 mm × 10 mm × 0.2 mm). The test was conducted in a 1 M KOH solution. Before the electrochemical test, the working electrode was sealed, exposing 0.64 square centimeters of working area. The non-working surface was encapsulated with waterproof PTFE tape and 704 silicone rubber to ensure that the current value automatically collected by the computer was the required current density. All electrochemical test data were collected in a constant temperature water bath. Before valid data testing, the open-circuit potential of the working electrode was measured using a three-electrode method. The open-circuit potential of the NiV electrode stabilized at approximately -0.6 V within 30 minutes. After the open-circuit potential stabilized, the corresponding data tests were performed on the electrode. The cathode overpotential test process is as follows: the value of the open circuit potential that is stable is selected as the first peak potential, and the value of the open circuit potential that drops by 2V is selected as the second peak potential. That is, the polarization test range is 2V, the scan rate is 4mV / s, the electrolytic cell parameters are selected according to the reference electrode parameters corresponding to mercury / mercury oxide, and then the test begins.

[0075] The cathode constant current polarization stability test process is as follows: select constant current polarization mode for testing, set constant current to -150mA, polarization time to 12h, test the potential of the sample for a long time, and observe the state of the sample at the same time.

[0076] The cathode CV test process: linear cyclic voltammetry was selected. The value of the open circuit potential that is stable was selected as the first peak potential, and the value that decreases by 0.1V from the open circuit potential was selected as the second peak potential. That is, the polarization test range is 0.1V. The scanning direction is positive, the number of cycles is 6, and the scanning rate is gradually increased from 10mVs to 100mVs. A total of 10 tests were performed.

[0077] The corrosion resistance is tested as follows: the open circuit potential in 1M KOH is used as the indicator. The more positive the potential value, the better the corrosion resistance of the material.

[0078] The yield strength was measured according to the Chinese national standard GB / T 228.1-2010.

[0079] Table 1

[0080] As shown in Table 1, the cathode overpotentials of the sintered porous metal materials in Examples 1-4 are all lower than those of the platinum and graphite electrodes, exhibiting better catalytic hydrogen evolution performance. Compared with the examples, the cathode overpotentials of Control Examples 1-3 are significantly increased, indicating that excessively low or high sintering temperatures and heating methods can significantly affect pore formation, thereby reducing the specific surface area and the number of catalytic active sites.

[0081] In addition to a significant reduction in cathode overpotential, the sintered porous metal materials of Examples 1-4 exhibit significantly better corrosion resistance and yield strength than those of Control Example 3. This demonstrates that the present invention, through a special sintering process, significantly improves the high content of intermetallic compounds, thereby significantly enhancing corrosion resistance and yield strength.

[0082] Compared with Example 3, although the cathode overpotential of Example 4 is reduced, the purity of the intermetallic compound in Example 4 is improved and the composition is uniform, so it has significantly better corrosion resistance and yield strength than Example 3.

[0083] Figure 6 The image shows the cathode constant current polarization stability test curve for the sintered metal porous material in Example 3. From... Figure 6 It can be seen that in a 1M KOH solution, when the fixed current density is -150 mA·cm⁻¹ -2 When the test time is 12 hours, the voltage fluctuation does not exceed 1.4%, indicating that the sintered metal porous material of Example 3 has good stability in catalytic hydrogen evolution performance as a cathode material in alkaline solution.

[0084] Figure 7 The CV cycle curve is shown for the sintered porous metal material of Example 3. Figure 8 This is the electric double-layer capacitor of the sintered porous metal material in Example 3. From... Figure 7-8It can be seen that the double-layer capacitance value C of the material is... dl It has a large specific surface area, providing abundant catalytic active sites.

[0085] Figure 9 SEM images of the sintered porous metal material from Example 3 (left image is a low-magnification image, right image is a high-magnification image). From Figure 9 It can be seen that the sintered metal porous material of Example 3 has three-dimensional interconnected pores and relatively abundant pores.

[0086] Figure 10 This is a backscattered scanning electron microscope (SSE) image of the sintered porous metal material from Example 3. From... Figure 10 It can be seen that the nickel and vanadium elements are relatively evenly distributed in the sintered metal porous material of Example 3.

[0087] The porosity of the sintered metal porous material of Example 3 was tested using the Archimedes method and found to be 38%.

[0088] The following are application examples of the sintered metal porous materials of the present invention.

[0089] Figure 11 This is a schematic diagram of the structure of the first embodiment of the electrolytic hydrogen production device of the present invention. Figure 12 for Figure 11 A schematic diagram of the section after cutting the AA section. Figure 13 for Figure 12 A schematic diagram of the electrolytic hydrogen production device from another angle. Figure 14 for Figure 11 A schematic diagram of the outer shape of the intermediate cathode. Figure 15 for Figure 11 A schematic diagram of the material layer structure of the central cathode. (See diagram below.) Figure 11-15 As shown, the electrolytic hydrogen production device includes: an electrolytic cell shell 11, an anode 12, and a cathode 13.

[0090] The anode 12 is installed inside the electrolytic cell housing 11 and is used to oxidize the electrolyte through an anodic electrochemical reaction. The anode 12 here can be the same as or similar to the anode in the electrocatalytic oxidation reactor (such as a titanium-based metal oxide coated electrode).

[0091] The cathode 13 is installed inside the electrolytic cell housing 11 and is used to generate hydrogen gas through a cathode electrochemical reaction. The cathode 13 is a hollow structure having a shell 131 and a hollow layer 132, and the hollow structure has an opening 133.

[0092] The main purpose of configuring the cathode 13 as a hollow structure with a shell 131 and a hollow layer 132 is to provide a hydrogen output channel through the hollow layer 132. Specifically, the hollow layer 132 provides a hydrogen output channel, and the opening 133 is used to output hydrogen from the hollow layer 132. The electrolytic cell shell 11 is provided with an exhaust structure, and hydrogen is output through the opening 133.

[0093] The shell layer 131 includes a cathode layer 1311 and a diaphragm layer 1312, which are integrally manufactured and arranged from the inside out. The cathode layer 1311 is a porous body with densely distributed three-dimensional interconnected pores, thereby increasing the specific surface area of ​​the cathode layer 1311, improving the efficiency of the cathode electrochemical reaction, and allowing hydrogen gas to enter the hollow layer 132 through the pores. The diaphragm layer 1312 is formed by a diaphragm material attached to the outer surface of the cathode layer 1311.

[0094] The porous body is a metallic porous material, which can further increase the specific surface area of ​​the cathode layer 1311. Specifically, the metallic porous material is the sintered metallic porous material in the above embodiments.

[0095] Typically, the porous body is used to connect to the negative terminal of a DC power supply, and the anode 12 is used to connect to the positive terminal of a DC power supply.

[0096] Therefore, since the cathode 13 is a hollow structure with a shell 131 and a hollow layer 132, and the hollow structure has an opening 133, the shell 131 includes a cathode layer 1311 and a diaphragm layer 1312 manufactured as a single unit and arranged from the inside out. The cathode layer 1311 is a porous body with numerous pores, which is used to connect to the power source. The diaphragm layer 1312 is formed by a diaphragm material attached to the outer surface of the cathode layer 1311. The hollow layer 132 provides a hydrogen output channel, and the opening 133 is used to output hydrogen. Thus, the diaphragm and cathode are integrated. For electrolytic hydrogen production, this allows for the separate recovery of hydrogen and helps simplify the structure of the electrolytic hydrogen production device.

[0097] Furthermore, since the diaphragm layer 1312 is made of diaphragm material attached to the outer surface of the cathode layer 1311 to form a diaphragm, the diaphragm layer 1312 (i.e., the diaphragm) also acts as a filter membrane on the outer surface of the cathode layer 1311, which can prevent particulate matter in the electrolyte from entering the cathode layer 1311 through the diaphragm layer 1312 and causing pore blockage of the cathode layer 1311.

[0098] The membrane material comprises an inorganic membrane. Generally, inorganic membranes are more easily and stably bonded to porous metallic materials. Optionally, the membrane material may comprise any one of a ceramic membrane, a polymer-ceramic hybrid membrane, or a nanocomposite membrane. Ceramic membranes, polymer-ceramic hybrid membranes, and nanocomposite membranes are all existing electrolyte membranes. The ceramic component may comprise alumina ceramic or silicon nitride ceramic.

[0099] Typically, the diaphragm layer 1312 itself and / or the diaphragm layer 1312 and the cathode layer 1311 can also form an asymmetric composite layer structure.

[0100] like Figure 11-15 In the first embodiment shown, the hollow structure is a plate-shaped hollow structure. Thus, the cathode 13 is a cathode plate, facilitating installation and use within the trough-shaped electrolytic cell housing 11. Based on this, as... Figure 14 As shown, typically, the opening 133 is provided on the sidewall of the plate-shaped hollow structure that forms the thickness of the plate-shaped hollow structure.

[0101] Figure 16 This is a schematic diagram of the anode and cathode in a second embodiment of the electrolytic hydrogen production apparatus of the present invention. Figure 17 for Figure 16 A schematic diagram of the structure shown from another angle. (See diagram below.) Figure 16 As shown, the hollow structure is a tubular hollow structure, and the end of the tubular hollow structure is provided with the opening 133. Meanwhile, the anode 12 is a cylindrical body and is fitted over the cathode 13.

[0102] The method for manufacturing cathode 13 may include the steps of: coating a slurry containing a diaphragm material onto the outer surface of a sintered porous metal material (which is controlled to have a plate-like hollow structure or a tubular hollow structure during pressing), and then sintering the sintered porous metal material coated with the slurry to form a diaphragm layer, which serves as a diaphragm when in use.

[0103] like Figures 11-15In the first embodiment shown, the electrolytic cell shell 11 is vertically mounted, and the electrolytic cell shell 11 has an electrolysis zone 111 and an air flotation zone 112 arranged sequentially from bottom to top; the anode 12 and the cathode 13 are arranged in the electrolysis zone 111, and an air flotation channel is provided between the anode 12 and the cathode 13. The air flotation channel is used to absorb the gas (such as oxygen) generated when the anode 12 oxidizes the water entering the electrolysis zone 111 through the anodic electrochemical reaction and / or the gas located in the electrolysis zone 111 within the electrolytic cell shell 11. Gas generated by aeration device 14 in the lower part of electrolysis zone 111 is introduced into flotation zone 112; when the airflow upward channel is used to introduce gas generated by aeration device 14 in the lower part of electrolysis zone 111 inside the electrolytic cell shell 11 into flotation zone 112, aeration device 14 is provided in the lower part of electrolysis zone 111 inside the electrolytic cell shell 11; a foam cleaning mechanism 15 is also provided at the top of flotation zone 112, and the foam cleaning mechanism 15 is used to discharge the foam generated at the top of flotation zone 112 into electrolytic cell shell 11.

[0104] Specifically, a water distributor 16 is provided inside the electrolytic cell shell 11 at the lower part of the electrolysis zone 111, and the water distributor 16 is used to introduce water. The water distributor 16 can be a pipe with numerous water outlet holes.

[0105] Specifically, the foam cleaning mechanism 15 includes an overflow weir, and the electrolytic cell shell 11 is provided with an overflow port that communicates with the overflow weir.

[0106] Therefore, the aforementioned electrolytic hydrogen production device also functions as an air flotation device to further enhance the water purification effect of the electrolytic hydrogen production device. Since the diaphragm layer 1312 is formed by a diaphragm material attached to the outer surface of the cathode layer 1311, the cathode layer 1311 is isolated from the airflow upward channel by the diaphragm. When aeration is performed by the aeration device 14, the air does not come into contact with the hydrogen, greatly reducing safety hazards.

[0107] In addition, a cathode mounting interface structure 113 is provided inside the electrolytic cell shell 11. The input part of the cathode mounting interface structure 113 is connected to the opening 133 through a sealed connection structure, and the output part of the cathode mounting interface structure 113 is connected to the exhaust structure.

[0108] The exhaust structure includes a gas-liquid separator 17 disposed on the electrolytic cell housing 11. The gas-liquid separator 17 has a gas-liquid separation chamber, which is connected to the opening 133 (through the cathode mounting interface structure 113). The gas-liquid separator 17 and the electrolytic cell housing 11 are connected through the opening 133. The gas-liquid separation chamber is connected to a return pipeline system (not shown in the figure), which is used to return the liquid in the gas-liquid separation chamber back to the electrolytic cell housing 11.

[0109] The gas-liquid separator 17 may also be equipped with a mechanical stirring and / or heating device to promote the evolution of hydrogen in the gas-liquid separator 17 and its discharge from the gas-liquid separator 17.

[0110] An embodiment of the electrolytic hydrogen production method of the present invention includes the following steps: using... Figure 11-15 The electrolytic hydrogen production apparatus of the first embodiment shown performs electrolysis in a 1M KOH solution. It has been verified that when the current density is 10 mA·cm⁻¹... -2 At that time, the cathode overpotential was 30–90 mV (vs. RHE), and the Tafel slope was 80–120 mV·dec. -1 (vs. RHE); at a constant 400 mA·cm -2 Electrolysis at a constant current density for 40–80 hours resulted in potential fluctuations of less than 30 mV after stabilization; at a constant current density of 10 mA·cm⁻¹, the potential fluctuations were all less than 30 mV. -2 Electrolysis was performed continuously at current densities for 72–120 hours, and the potential fluctuations after stabilization were all less than 20 mV. This demonstrates that the sintered porous metal material of this invention possesses both high catalytic activity in alkaline water electrolysis and good stability at high current densities, exhibiting excellent hydrogen evolution performance.

[0111] The specific implementation of the water treatment method of the present invention includes the following steps: (1) The wastewater is pretreated to obtain an electrolyte with a solid content of less than or equal to 1 mg / L, a salt content of ≤15 g / L, and a pH of 12 to 14; The pretreatment includes any of the following steps: a. treating the wastewater with air flotation and / or filtration to obtain an electrolyte with a solid content that meets the requirements for electrolysis; b. treating the wastewater with any of the following methods: softening, membrane separation, ion exchange, and electrodialysis to obtain an electrolyte with a salt content that meets the requirements for electrolysis; c. treating the wastewater with acidic or alkaline reagents to obtain an electrolyte with a pH that meets the requirements for electrolysis; d. adding chloride ions to the wastewater; e. performing adsorption treatment on the wastewater.

[0112] The solid content mainly refers to the suspended solids (SS) content, which refers to solid substances suspended in water, including inorganic and organic matter that are insoluble in water, as well as mud, sand, clay, microorganisms, etc.

[0113] The salt content mainly refers to the content of strong electrolytes dissolved in water, usually expressed as total dissolved solids (TDS), which refers to the total amount of all solutes in water, including both inorganic and organic matter. The higher the TDS value, the more dissolved substances are contained in the water.

[0114] (2) The electrolyte is fed into the electrolytic cell of the electrolytic hydrogen production device for electrolytic treatment, decomposing the organic matter in the electrolyte and generating hydrogen; The organic matter mentioned includes COD and BOD. COD (Chemical Oxygen Demand) refers to the amount of reducing substances in a water sample that need to be oxidized, measured by chemical methods. BOD (Biochemical Oxygen Demand) refers to the amount of dissolved oxygen consumed by microorganisms in decomposing certain oxidizable substances (especially organic matter) in a certain volume of water within a certain period.

[0115] (3) The liquid after electrolysis is treated for valuable resource recovery and then discharged as product water. The valuable resource recovery and treatment includes concentration treatment and evaporation crystallization treatment. And / or, the liquid after electrolysis is treated for impurities and then discharged as product water. The impurity removal treatment includes any of the following: softening treatment, filtration treatment and disinfection treatment.

[0116] The first embodiment of the water treatment method of the present invention is the treatment of lithium extraction wastewater from salt lakes using an extraction method. Figure 18 This is a schematic diagram of the water treatment system structure used in the first embodiment of the water treatment method of the present invention. Figure 19 This is a schematic diagram of the process for lithium extraction from salt lakes using the extraction method.

[0117] like Figure 18-19 As shown, lithium extraction from salt lakes via extraction involves extracting lithium from salt lake brine with a molar ratio of Mg / Li ≥ 8 after the extraction of non-lithium salts, including potassium and sodium salts. The wastewater from lithium extraction via extraction consists of an aqueous extraction phase, a washing liquid, and an acid washing liquid. The aqueous extraction phase is the aqueous phase obtained after extraction of the salt lake brine; the washing liquid is the washing liquid obtained after washing the organic phase obtained after extraction of the salt lake brine; and the acid washing liquid is the acid washing liquid obtained after washing, back-extraction, and regeneration of the organic phase obtained after extraction of the salt lake brine. The main water components of the wastewater from lithium extraction via extraction are organic matter (including COD and BOD), SS, and Cl. - Li + CO32- Along with some other high-valence heavy metal ions and surfactants, the organic matter content is 400 mg / L. COD (Chemical Oxygen Demand) refers to the amount of reducing substances in a water sample that need to be oxidized, measured chemically. BOD (Biochemical Oxygen Demand) refers to the amount of dissolved oxygen consumed by microorganisms in decomposing certain oxidizable substances (especially organic matter) in a given volume of water over a specific period.

[0118] The water treatment system for treating lithium extraction wastewater from salt lakes using the extraction method described above includes a pretreatment unit, an electrolytic hydrogen production unit, and a valuable resource recovery and treatment unit. The pretreatment unit includes an air flotation device, a first adsorption device, a filtration device, and a pH adjustment tank. The valuable resource recovery and treatment unit includes a second adsorption device, a concentration device, and an evaporation and crystallization device.

[0119] The flotation device is used to treat wastewater by flotation and output scum and a first liquid. The first adsorption device is used to adsorb impurities in the first liquid that include at least surfactants and output a second liquid; the first adsorption device uses activated carbon as the adsorbent. The filtration device is used to filter the second liquid and output a third liquid. The pH adjustment tank is used to adjust the pH of the third liquid with sodium hydroxide and output a fourth liquid (i.e., electrolyte). The resulting electrolyte has a solids content (SS) of less than or equal to 1 mg / L, a total salinity (TDS) of ≤15 g / L, a pH of 12–14, and a surfactant content of ≤100 ppm.

[0120] The electrolysis hydrogen production unit adopts the above-mentioned... Figure 11-15 The electrolytic hydrogen production apparatus of the first embodiment shown electrolyzes the fourth liquid. The electrode voltage of the electrolytic cell is kept constant at 3.5V, generating a current of 7.5A. Due to the electrolytic reaction, the current changes over time. Electrolysis at a constant voltage of 3.5V for 24 hours not only produces hydrogen with a purity ≥97% and a hydrogen flow rate ≥1026mL / h, indicating high hydrogen purity and high hydrogen production efficiency, but also results in the fifth liquid obtained after electrolysis having an organic matter content ≤100mg / L, indicating high organic matter decomposition efficiency.

[0121] The second adsorption device is used to adsorb lithium onto the fifth liquid and output the sixth liquid; the concentration device uses a reverse osmosis membrane to concentrate the sixth liquid and output the concentrate and permeate; the evaporation crystallization device is used to evaporate and crystallize the concentrate and output the lithium product.

[0122] A second embodiment of the water treatment method of the present invention is the treatment of papermaking wastewater. Figure 18This is a schematic diagram of the water treatment system structure used in the second embodiment of the water treatment method of the present invention.

[0123] like Figure 20 As shown, the water treatment system includes a pretreatment unit, an electrolysis hydrogen production unit, and a purification unit. The pretreatment unit includes a first filtration device, a softening device, and a pH adjustment tank. The purification unit includes a disinfection device and a second filtration device.

[0124] The first filtration device is used to filter wastewater to remove impurities with a particle size greater than or equal to 5 μm and output a first liquid. The first filtration device includes a coarse and fine screen and a first microfilter connected in one step. The softening device is used to soften the first liquid to remove polyvalent metal ions and oil impurities and output a second liquid. The softening device includes a coagulation sedimentation tank, a filter press, and a second microfilter. The first liquid reacts with flocculant and precipitant in the coagulation sedimentation tank to generate a flocculated sediment, which is then filtered by the filter press and the second microfilter to obtain the second liquid. The pH adjustment tank is used to adjust the pH of the second liquid with sodium hydroxide and output a third liquid that can be used as an electrolyte. The resulting electrolyte has a solid content (SS) of less than or equal to 1 mg / L, a salt content of ≤15 g / L, and a pH of 12–14.

[0125] The electrolysis hydrogen production unit adopts the above-mentioned... Figure 11-15 The electrolytic hydrogen production apparatus of the first embodiment shown electrolyzes a third liquid. The electrode voltage of the electrolytic cell is kept constant at 3.5V, generating a current of 7.5A. Due to the electrolytic reaction, the current changes over time. Electrolysis at a constant voltage of 3.5V for 36 hours not only produces hydrogen with a purity ≥97% and a hydrogen flow rate ≥1014mL / h, indicating high hydrogen purity and efficiency, but also results in an organic matter content ≤80mg / L in the fourth liquid obtained after electrolysis, demonstrating high organic matter decomposition efficiency. In the initial stage of electrolysis, a small amount of sodium chloride is added to the electrolytic cell of the electrolytic hydrogen production apparatus to provide recyclable chloride ions.

[0126] The disinfection equipment is used to disinfect the fourth liquid and output the fifth liquid; the disinfectant used in the disinfection equipment is any combination of chlorine, chlorine dioxide, ozone, ultraviolet light, and high-valence manganese. The second filtration equipment is used to filter the fifth liquid to remove impurities with a particle size greater than or equal to 0.5 μm and output reused product water; the second filtration equipment includes a third microfilter.

[0127] The aforementioned papermaking wastewater refers to the wastewater discharged from paper mills, mainly including pulping wastewater and / or papermaking white water. The papermaking process primarily includes pulping, conditioning, and papermaking finishing. Pulping is the first step in the papermaking process. The most common pulping process involves directly cooking wood or waste paper using caustic soda and sulfate methods to obtain a mixture of wood pulp and black liquor. After multiple stages of washing, black liquor and wood pulp are obtained separately. The wood pulp then undergoes multiple stages of bleaching and washing to obtain papermaking pulp. The conditioning process of the papermaking pulp is another key aspect of the papermaking process. The strength, color, printability, and shelf life of the finished paper product are directly related to the conditioning process. Common conditioning processes can be broadly divided into loosening, beating, sizing, and filling. After conditioning, the pulp undergoes weaving, dewatering, drying, calendering, and cutting processes to obtain the final paper product.

[0128] Pulping wastewater mainly consists of condensate wastewater and washing wastewater. Black liquor contains a large amount of organic matter such as alkali lignin, hemicellulose, and cellulose decomposition products, as well as various sodium salts. It needs to be treated through multi-effect evaporation, combustion, re-dissolution, and causticization processes to obtain white liquor that can participate in the cooking process. This process will generate a lot of condensate wastewater. At the same time, a lot of washing wastewater will also be generated during the multi-stage washing process.

[0129] Because a large number of additives are typically used in the papermaking process to adjust the properties of paper products, the white water produced during papermaking contains a large amount of suspended solids such as fibers, fillers, and coatings. To reduce pollution and conserve water, it is usually partially or completely recycled. However, long-term recycling leads to the accumulation of various pollutants in the white water, resulting in very high levels of organic pollutants in the wastewater discharged from paper mills.

[0130] The working principle of air flotation equipment is as follows: A large number of highly dispersed microbubbles are introduced into the wastewater using a microbubble generator (usually requiring the addition of coagulants such as PMA and / or PAC). These microbubbles act as carriers, adhering to suspended particles (oil droplets) or flocs in the wastewater, forming a floating mass with an overall density less than the wastewater. This mass rises to the surface due to buoyancy, forming scum which is then removed, ultimately achieving wastewater purification. The air flotation equipment mainly includes an air flotation machine, preferably a high-efficiency shallow air flotation machine with a processing capacity of 5m³. 3 The unit has a capacity of 2.2kW per hour and is equipped with a microbubble generator, a slag scraper, and a coagulant feeding device.

[0131] In addition to using the aforementioned air flotation equipment, filtration equipment, and softening equipment for wastewater pretreatment, any combination of nanofiltration equipment, ion exchange equipment, and electrodialysis equipment can be used to treat wastewater to intercept polyvalent metal ions, thereby ensuring that the salt content of the electrolyte meets the electrolysis requirements.

[0132] In the above water treatment system, two-stage electrolysis hydrogen production devices can be added. When the organic matter content in the water does not meet the standard after electrolysis by the first-stage electrolysis hydrogen production device, the second-stage electrolysis hydrogen production device can be used to continue electrolysis treatment.

[0133] The foregoing has described the relevant content of the present invention. Those skilled in the art will be able to implement the present invention based on these descriptions. All other embodiments obtained by those skilled in the art based on the above description of the present invention without inventive effort should fall within the scope of protection of the present invention.

Claims

1. A method for preparing sintered porous metal materials, wherein the sintered porous metal materials are composed of Ni and V, the metal elements mainly existing as intermetallic compounds, wherein the intermetallic compounds are Ni3V and Ni2V3; or, the intermetallic compound is Ni2V; or, the intermetallic compound is Ni2V and NiV3; characterized in that: The preparation method includes the following steps: Ni powder and V powder are ball-milled and mixed to obtain a mixed powder; Add a forming aid to the mixed powder, then granulate and sieve to obtain shaped granules; The shaped particles are pressed into shape to obtain a blank; The billet is subjected to high-temperature sintering treatment, and then cooled in the furnace to obtain sintered metal porous material; The high-temperature sintering process is as follows: First stage: Raise the temperature from room temperature to 300-400℃ and hold for 40-80 minutes; Second stage: Continue to heat to 450-500℃ and hold for 40-80 minutes; Third stage: Continue to raise the temperature to 550-600℃ and hold for 40-80 minutes; Fourth stage: Continue to raise the temperature to 650-700℃ and hold for 40-80 minutes; Fifth stage: Continue heating to 750-800℃ and hold for 40-80 minutes; Stage 6: Continue heating to 850–900℃ and hold for 40–80 minutes; Stage 7: Continue heating to 950–1050℃ and hold for 80–230 minutes.

2. The method for preparing sintered porous metal materials as described in claim 1, characterized in that: The particle size of Ni powder and V powder is 3-20 μm; the forming aid is stearic acid or polyvinyl butyral, and the amount of forming aid is 2-5% of the mass of the mixed powder; sieving is done with a 40-80 mesh sieve; and the powder is pressed and formed under a pressure of 50-300 MPa.

3. The method for preparing sintered porous metal materials as described in claim 1, characterized in that: The seventh phase is divided into two stages, as follows: Stage 1: Continue heating to ≥950 and ≤1000℃, and hold for 40–80 minutes; Phase 2: Continue heating to >1000 and ≤1050℃, and hold for 80-150 minutes.

4. The method for preparing sintered metal porous materials as described in claim 3, characterized in that: The heating rate for the first stage to stage 1 is 4–6 °C / min, and the heating rate for stage 2 is 2–4 °C / min.

5. A sintered porous metal material, characterized in that: It is prepared by the preparation method according to any one of claims 1-4.

6. An electrolytic hydrogen production apparatus, comprising a cathode, characterized in that: The cathode is prepared using the sintered metal porous material prepared by any one of claims 1-4, or the sintered metal porous material prepared by claim 5.

7. A method for producing hydrogen by electrolysis, characterized in that: The procedure includes: electrolyzing alkaline water using the electrolytic hydrogen production device described in claim 6.

Citation Information

Patent Citations

  • Preparation method of nickel-based alloy electrolysis hydrogen evolution cathode porous material

    CN108247060A

  • Preparation method of pre-alloyed porous nickel-based electrolytic hydrogen evolution cathode material

    CN109267084A

  • Nickel or nickel alloy porous material with directional holes, preparation method thereof and application thereof in a hydrogen evolution electrode

    CN110714140A